SHG Banking in India: The evolution of a rural financial innovation - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2005)
Linking banks and self-help groups has been a major program of German development cooperation since the mid-1980s. Given the involvement of GTZ in SHG banking and the outreach of that program in India, the German Ministry of Economic Cooperation and Development (BMZ) has proposed to study the impact of SHG banking in India in the framework of the United Nations Millennium Development Goals 2015 on the basis of the existing literature; and subsequently to examine the contribution of GTZ on the evolution of the program in India. The results of the impact studies indicate that considerable socio-economic benefits have been accruing to small-scale farming households, rural micro entrepreneurs and the landless and have contributed to most impact aspects of MDGs 1 to 6. Most SHG members substantially increase their saving rates. A shift has been observed over time from consumption loans to loans for income generating purposes. Increased savings and capital formation improve the self-financing capacities and even out the household?s cash flow. This in turn has improved their risk absorption capacity and made them less vulnerable. Access to formal finance has substantially reduced dependency on money lenders and has diminished capital costs. The improved access to financial services has benefited SHG members and their households in maintaining, intensifying and diversifying their economic activities, with positive effects on income and employment generation, especially in the non-agricultural sector. The unprecedented scale of SHG banking and its enormous potential for further growth, within India and without, raises the question as to the dynamics of its evolution, the forces behind it, and the contribution of external organizations. How did it evolve, what kept it growing, and what has been the role of GTZ? The study is mainly based an analysis of documents of APRACA, GTZ and NABARD in the archives of the Development Research Center (AEF) of the University of Cologne and on discussions in March 2005 with key personnel.
Keywords: 330